Thermo-electric effects in a Luttinger liquid - Krive, I.V.; Romanovsky, I.A.; Bogachek, E.N.; Scherbakov, A.G.; Landman, Uzi (Физика низких температур, 2001)
Thermoelectric effects in a Luttinger liquid (LL) wire

adiabatically connected to the leads of noninteracting electrons are considered. For a

multichannel LL a staircase-like behavior of the thermal conductance as a function of

chemical potential is found. A thermopower for a LL wire with an impurity is evaluated for

two cases: (i) LL constriction and (ii) infinite LL wire. We show that the thermopower is

described a Mott-like formula renormalized by an interaction-dependent factor. For an

infinite LL the renormalization factor decreases with increase of the interaction. However,

for a realistic situation, when a LL wire is connected to the leads of noninteracting

electrons (LL constriction), the repulsive electron-electron interaction enhances the

thermopower. A nonlinear Peltier effect in a LL is briefly discussed.